Impact of viral eradication by direct‐acting antivirals on the risk of hepatocellular carcinoma development, prognosis, and portal hypertension in hepatitis C virus‐related compensated cirrhosis patients. Issue 11 (7th September 2020) - Nagaoki, Yuko; Imamura, Michio; Teraoka, Yuji; Morio, Kei; Fujino, Hatsue; Ono, Atsushi; Nakahara, Takashi; Murakami, Eisuke; Yamauchi, Masami; Kawaoka, Tomokazu; Miki, Daiki; Tsuge, Masataka; et al.
Abstract : Aim: We analyzed the impact of hepatitis C virus eradication by direct‐acting antiviral (DAA) therapy on the risk of development of hepatocellular carcinoma (HCC), prognosis, and portal hypertension in patients with liver cirrhosis. Methods: The rate of HCC development and overall survival after achievement of sustained virological response (SVR) in 173 DAA‐treated compensated cirrhosis patients without HCC history were retrospectively compared with that of 125 cirrhosis patients who achieved SVR by interferon (IFN)‐based therapy or that of 85 cirrhosis patients who failed to respond to anti‐HCV therapy. Changes in esophagogastric varices (EGV) and incidence of portosystemic encephalopathy were analyzed in 87 consecutive cirrhosis patients. Results: The cumulative HCC development rates at 1, 3, and 5 years were 2%, 7%, and 7% for the DAA‐SVR group, significantly lower than the 3%, 7%, and 18% for the non‐SVR group (log–rank, P  < 0.001). The cumulative overall survival rates were also significantly improved in the DAA‐SVR group compared to the non‐SVR group (log–rank, P  < 0.001). These rates were similar between DAA‐SVR and IFN‐SVR groups ( P  = 0.121 and 0.261, respectively). Esophagogastric varices were aggravated, and portosystemic encephalopathy occurred in a subset of cirrhosis patients who achieved SVR by DAA therapy. These events were more frequent in patients with large feeding vessels for EGV and portosystemic shunts at the time of SVR. Conclusion: Achievement of SVR by DAA therapy reduces the risk of HCC development and prolongs survival, similar to theresults achieved with IFN‐based therapy, but portal hypertension is not immediately improved in compensated liver cirrhosis patients.